OUTLINING TECHNIQUE ON STUDENTS’ ABILITY TO WRITE RECOUNT TEXT - Siti Rochimah (STKIP PGRI Tulungagung, 2023)
This research aims at finding out the effectiveness of outlining technique toward students’ ability to write recount text. The research design of this study is quasi-experiment. The subject of this research is the tenth-grade students of SMKN 2 Boyolangu. The researcher takes two classes, namely experimental group and control group. The number of students from the experimental group is 36 students and control group is 36 students. Then, the total of students is 72 students. The results of the research showed that: the tenth-grade students before using outlining technique shows that the mean score is 22.17 and after being treated by using outlining technique the mean score is 62.58. There is a significant difference between the students before being taught by using SMKN 2 Boyolangu and after being taught by using outlining technique. Then, the result of statistical computation Independent Sample Mann Whitney U Test by using SPSS shows that outlining technique method is effective. The significant value of the data is 0.000. It means that 0.000 lower than 0.05. Therefore, the null hypothesis is rejected. It can be concluded that outlining technique is effective to be implemented to the students at tenth grade of SMKN 2 Boyolangu. Because, those who are taught using outlining technique shows better writing skill than those who are not taught using outlining technique. From the research findings, there are some suggestions recommended by the researcher. For teachers, the teachers get new technique especially in teaching writing. The future researchers can get additional information about outlining technique.